Current Issues in Natural Resource and Environmental Economics - Halkos, George (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The interrelationship between economic growth, efficient use of natural resources, and sustainability has been of great interest to economists, researchers and policy makers. Knowledge of actual causality direction between sustainability, efficiency and growth has important implications for modeling environmental economic policies. Various serious environmental problems demand urgent attention and planning of adequate policies towards sustainability. Development of new economic and environmental policies and use of new econometric, operational research and mathematical and statistical techniques offers scope for further research. Studies were invited to address economic growth and environment: environmental problems; Air/water pollution; Health impact of pollution; Waste management; Natural resources management; Population economics; Environmental policy tools; Renewable energy sources; Business and sustainable development; Sustainable transport; Sustainable tourism; Urban and regional development.